Low-Dose Interleukin-2 Altered Gut Microbiota and Ameliorated Collagen-Induced Arthritis - Li N; Li X; Su R; Wu R; Niu HQ; Luo J; Gao C; Li X; Wang C (Dove Medical Press, 2022)
Na Li,1 Xuefei Li,1 Rui Su,1 Ruihe Wu,1 Hong-Qing Niu,1 Jing Luo,1 Chong Gao,2 Xiaofeng Li,1 Caihong Wang1 1Department of Rheumatology, The Second Hospital of Shanxi Medical University, Taiyuan, Shanxi, People's Republic of China; 2Pathology, Joint Program in Transfusion Medicine, Brigham and Women's Hospital/Children's Hospital, Harvard Medical School, Boston, MA, USACorrespondence: Caihong Wang, Tel +8613603515399, Fax +863513365551, Email snwch@sina.comPurpose: Low-dose interleukin-2 (ld-IL-2) has been shown to regulate the balance between effector T and regulatory T (Treg) cells and has been used in several clinical trials to treat autoimmune diseases including rheumatoid arthritis (RA). In this study, we investigated the effects of ld-IL-2 on collagen-induced arthritis (CIA) in mice.Methods: Arthritis severity in CIA mice was measured using the arthritis index (AI), radiographs, and hematoxylin and eosin staining. Cytokines were detected using enzyme-linked immunosorbent assay. Gut microbiota alterations and short-chain fatty acid production were analyzed through 16S rRNA sequencing and gas chromatography.Results: The AI scores of CIA mice treated with ld-IL-2 were significantly lower compared to the model group, which significantly reduced the severity of arthritis. Ld-IL-2 also altered the gut microbiota in CIA mice. The diversity, composition, and dominant species of gut microbiota were altered by ld-IL-2 treatment. Ld-IL-2 also increased short-chain fatty acid levels. There was a strong correlation between ld-IL-2 treatment and improved gut microbiota.Conclusion: Ld-IL-2 significantly ameliorated joint inflammation and bone damage and improved gut microbial dysbiosis in CIA, indicating that it may be a promising therapy for RA patients.Keywords: low-dose IL-2, CIA, gut microbiota, SCFA, 16sRNA